When Analysts Talk, Do Institutional Investors Listen? Evidence from Target Price Changes. Issue 2 (May 2016) - Lin, Shannon; Tan, Hongping; Zhang, Zenan
Abstract: We find that institutions trade in the same direction as target price changes based on 6, 415 U.S. firms from 1999 to 2011, even after controlling changes in stock recommendations and earnings forecasts. The impact of target price changes on institutional trading is more pronounced for small firms, firms followed by few analysts, and illiquid firms, and is mainly limited to transient institutions. We do not find any outperformance for institutions to follow analysts' target price forecasts, suggesting that institutions could find it easier to justify their investment decisions by following analyst forecasts, although such trading does not result in outperformance.